(untitled) (Research, Society and Development, 2025)
Soil and water contamination generates major environmental problems and, consequently, public health issues. This largely occurs due to the inadequate disposal of raw sewage into the environment, potentially affecting public health. This reality occurs more frequently in rural areas due to the lack of a sewage system in these regions, while most Brazilian municipalities are served by sewage collection and treatment in urban areas. Therefore, this study aimed to identify the similarities between the methods, the implementation cost, as well as the efficiency in meeting the physicochemical parameters established by CONAMA Resolution No. 430/2011. The methodology used was bibliographic research of works seeking a descriptive qualitative approach. The results demonstrated that the configuration for implementing the system needs to consider factors such as soil slope, daily sewage flow, and efficiency in meeting the parameters required by current legislation. Finally, it was found that the WCFV (Wastewater Treatment Plant) inserted in rural communities is economically viable compared to the other systems studied; however, the generation of clogging must be taken into consideration, a problem that can be reduced with the insertion of a post-treatment such as WCFH (Wastewater Treatment Plant with Hydrogenated Sewage).